Bat Diversity in Imbak Canyon Conservation Area: Note on their Echolocation Calls and Ectoparasites - Juliana Senawi; Azniza Mahyudin; Ummu Safiyah Daud; Amirrah Amat; Simon Lagundi; Eric Gondilang; Erwan Sutail; Saiful Narimin; Isham Azhar (Universiti Malaysia Sabah, 2020)
Imbak Canyon Conservation Area (ICCA) is one of the conservation areas managed by the Sabah Foundation, which comprise of mixed vegetation forest landscape. A bat survey was conducted at ICCA from August 16th to 26th, 2017. A total of 141 individuals of bats representing 17 species were recorded from the eight nights of mist netting and harp trapping at various sites within the conservation area. Echolocation calls from 120 individuals of insectivorous bats representing 13 species were recorded, with 90% accuracy in relative amount. The captured bats were screened for ectoparasites from Order Diptera (91%), Mesostigmata (5%) and Ixodida (1%), and indicate that there is 66.7% prevalence. The results from the survey are paramount in enhancing information and knowledge on Bornean bats and their obligate ectoparasites.